(untitled) (Research, Society and Development, 2021)
The management of orbital fractures in children and adolescents is little reported in the literature, considering that orbital fractures can cause functional problems such as enophthalmia, diplopia and aesthetic deformities. The aim of this study is to review the literature and report three clinical cases, corroborating with professional experience, about the different management of orbital fractures in adolescents, approaching the advantages, disadvantages and complications. Among the different fractures of the orbital floor, the techniques of interposition of autograft of the anterior wall of the maxillary sinus, suture for anchoring the periosteum, and reduction and stabilization of the fracture by means of titanium mesh fixation were performed. The choice of material and technique depends on the surgeon’s preference, access and availability of materials. Regardless of which technique and material is used, and complete removal of the herniated tissue is fundamental to obtain satisfactory results.